Pengaturan Alih Fungsi Lahan Fasilitas Umum Yang Tidak Sesuai Peruntukannya Dikawasan Perumahan Bibis Karah Surabaya - Makhfudz Hidayatullah; Sri Setyadji (Lembaga Pengembangan Kinerja Dosen, 2024)
Housing is a collection of houses as part of settlements, both urban and rural, which are equipped with public infrastructure, facilities and utilities as a result of efforts to provide livable houses. If you look at the definition of housing, you can see that infrastructure, facilities and public utilities are requirements that must be completed in housing. In fact, when the housing is still under construction, housing marketing through a preliminary sale and purchase agreement system can only be carried out after there is certainty about several things, one of which is the availability of infrastructure, facilities and public utilities. Quantitative data from interview results is described in a frequency table qualitatively and descriptively. The data that has been obtained through research activities is analyzed qualitatively. Qualitative analysis is used to describe the data obtained, both primary data and secondary data, which is then followed by interpretation and conclusions. Implementation of the procurement of public facilities and social facilities is a mandatory requirement that must be provided by the developer/developer to obtain a building construction permit (IMB) from the Spatial Planning and Building Service. Where housing is a collection of houses as part of settlements, both urban and rural, which are equipped with infrastructure, facilities and public utilities as a result of efforts to provide livable houses. The development of housing infrastructure, facilities and public utilities is carried out by the Government, regional governments and/or every person. So the responsibility of the Surabaya City Regional Government for social facilities and public facilities in residential and residential areas is to carry out management, namely, by utilizing these facilities according to their intended use and by carrying out maintenance so that these facilities can be used optimally by residents.